Persepsi Masyarakat Nelayan Terhadap Kegiatan Reklamasi Wilayah Pesisir - Andi Tenri Oddang; La Ode Amaluddin; La Ode Nursalam (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2023)
Mata Village is one of the coastal areas which is the main route connecting urban areas to tourist sites in Kendari City. The aims of this study were to: 1) describe the perceptions of fishing communities towards the reclamation of the coastal area of Kelurahan Mata, Kendari City; and 2) describe the impact of reclamation on the coastal area of Kelurahan Mata, Kendari City. This study used quantitative methods with 30 respondents. Data collection techniques used are questionnaires, observation and documentation. The results of this study indicate that: 1) fishermen who state that reclamation activities in the coastal area of Mata Village affect their activities as fishermen; 2) reclamation impacts, namely: a) reviving water transportation; b) opening opportunities for development of coastal areas; c) increase regional income; d) damage part of the marine environment; and e) livelihoods of fishermen are disrupted.